Multiple Galactic Sources with Emission Above 56 TeV Detected by HAWC - Albert, A.; Alfaro, R.; Avila Rojas, D.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Capistran, T.; Carraminana, A.; Casanova, S.; Cotti, U.; Cotzomi, J.; Coutino De Leon, S.; et al. (Physical Review Letters, 2020)
We present the first catalog of gamma-ray sources emitting above 56 and 100 TeV with data from the High Altitude Water Cherenkov Observatory, a wide field-of-view observatory capable of detecting gamma rays up to a few hundred TeV. Nine sources are observed above 56 TeV, all of which are likely galactic in origin. Three sources continue emitting past 100 TeV, making this the highest-energy gamma-ray source catalog to date. We report the integral flux of each of these objects. We also report spectra for three high-estenergy sources and discuss the possibility that they are PeVatrons.
CRIS-Team WoS Importer:2020-01-31